"I'm able to put my thoughts into picturing them physically" - Phenomenological experiences of Dance Movement Psychotherapy in a Secondary School: Unexpected empowerment over external contingency. (July 2019) - Parsons, Ailsa; Dubrow-Marshall, Linda
Highlights: Three UK secondary school pupil-clients and five educators were interviewed following participation Dance Movement Psychotherapy. Phenomenological analysis revealed two thematic motifs and a series of subthemes emerged: unexpected empowerment and external contingency . Findings highlight key challenges and opportunities for practitioners of arts psychotherapies. Abstract: This study explored eight secondary school participants' subjective experiences of Dance Movement Psychotherapy [DMP], and how these perceptions relate to prior expectations and/or perceived outcomes from the therapy. How pupils and staff experience psychotherapeutic provision is of particular importance to engagement and process, with implications for therapeutic outcomes and – accordingly – the success and proliferation of such services within educational settings. A qualitative methodology based on Interpretative Phenomenological Analysis was utilised to explore these topics from the phenomenological lived experience of three pupil-clients and five staff involved. Experiences of 'unexpected empowerment' were most prominent along with related subthemes, and a differing notion of 'External Contingency' and its subthemes. Where clients did not expect to be provided with structured solutions or advice, their experiences of unexpected empowerment optimised the insight-based aspects of DMP. Alternatively, for a client anticipating a process resembling being led in a solution-oriented 'package', the client found it difficult to overcome dependency on – and seeking from – external influences as a resolution for subjective wellbeing. These results are discussed in the context of creative psychotherapies and wider social structures.